Broadband a go-go. - Cherry, S.M (IEEE spectrum)
In city after city, high-speed wireless access may be the next Internet revolution. The author discusses the use of a Dell laptop outfitted with a prototype card that communicates with a test network set up by broadband wireless start-up MeshNetworks Inc. for exploiting wireless Internet technology. Even at speed-limit speeds, the Mesh network held up, with download data rates of at least 500 kb/s. Mesh, along with Ricochet and other wireless point-to-point networks, are the best hope for a fully mobile future - a world where we can teleconference each other, watch news and entertainment in real time, order from online catalogs, pay our bills, and answer e-mail - anywhere, anytime, on ever smaller and sleeker handheld devices powered by ever more powerful microprocessors and software.